PENGARUH LATIHAN BEBAN KETTLER DAN LATIHAN BERBEBAN KARET TERHADAP JAUHNYA TENDANGAN BOLA DALAM PERMAINAN SEPAKBOLA DITINJAU DARI DAYA LEDAK TUNGKAI PADA SISWA SMA NEGERI 8 MAKASSAR - Bismar, Ahmad Rum (UNIVERSITAS NEGERI MAKASSAR, 2018)
This research is a field experiment with a 2 x 2 factorial design. The population and sample are male students of Makassar 8 Public High School with a total of 60 people. The data analysis technique used was Analysis of Variance (ANOVA) at a significant level of 95%. By looking at the existing problems, the results obtained from the processing of data show that: There is a significant difference in influence between kettler weight training and rubber load training on the distance of the ball kick in soccer games (Fo = 2.484> Ft = 4.03). There is a significant difference between high limb explosive power and low limb explosive power to the distance of the ball kick in soccer games in students (Fo = 4.469> Ft = 4.03). For students who have high limb explosive power, there is a significant difference between kettler weight training and rubber load training on the distance of the ball kick in soccer games (to = 13,829> tt = 2,048). For students who have low limb explosive power, there is a significant difference between kettler weight training and rubber load training on the distance of the ball kick in soccer games (to = 2.763> tt = 2.048)